Formulasi Masker Peel Off Gel dari Kombinasi Minyak Atsiri Sereh dan Cengkeh untuk Menghambat Bakteri Penyebab Jerawat - Manus, Noriko; Taurhesia, Shelly; Setyahadi, Siswa; Manus, Widya Christine (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2024)
Acne is a chronic skin disease involving inflammation of the pilosebaceous units with the main bacteria Staphylococcus epidermidis and Propionibacterium acnes has prompted the creation of cosmetic masks containing antibacterial agents. This study aims to evaluate the antibacterial activity of Lemongrass and Clove essential oils and to determine the synergistic effects of combining these essential oils in a peel-off gel mask formulation. The study was conducted using the liquid dilution method to determine the minimum inhibitory concentration and the disk diffusion method to test the inhibition zone diameter. Additionally, tests are conducted to determine the antibacterial activity against Propionibacterium acnes and Staphylococcus epidermidis, as well as to analyse the stability of the product both chemically and physically during storage. The results of the study showed that (1) the formulation containing a combination of 25% lemongrass and 18% cloves showed high inhibitory power and good stability, but caused moderate irritation; (2) lemongrass and clove essential oils were effective against Propionibacterium acnes and Staphylococcus epidermidis, but it was recommended to reduce the active ingredients to prevent potential irritation.